Optimal immigration policy: permanent, guest worker, or mode IV? - Maurice Schiff (Institute for the Study of Labor (IZA), 2007)
Immigration continues to be on the forefront of the policy debate on both sides of the Atlantic. A number of reforms of permanent and guest-worker (GW) immigration programs are being considered, and the temporary movement of service providers under Mode IV (GATS) is being negotiated at the Doha Round of the WTO. This paper contributes to the debate by examining these programs in a model where the host country government maximizes its objective function with respect to three policy instruments: the share of migrants' deferred income payment, the value of the bond employers must post and forfeit if GWs overstay, and the size of the program. Circular migration and illegal GWs' status regularization are considered. The paper shows that i) the optimal value of the bond is zero, ii) Mode IV is preferable to GW migration; iii) the optimal policy package consists of Mode IV and permanent migration, and iv) incorporating circular migration improves the policy package. Additional policy implications are also provided.
Keywords: 330; Immigration; guest-worker; Mode IV; permanent; overstaying; Migrationspolitik; Ausländische Arbeitskräfte; Internationale Arbeitsmobilität; Dienstleistungsberufe; GATS; Wohlfahrtseffekt; Theorie; Welt